Impacts of COVID‐19 induced income and rice price shocks on household welfare in Papua New Guinea: Household model estimates - Schmidt, Emily; Dorosh, Paul A.; Gilbert, Rachel (International Association of Agricultural Economists, 2021)
Concerns over the potential effects of the COVID‐19 pandemic have led to trade restrictions by major rice exporters, contributing to an average 25% increase in Thai and Vietnamese rice export prices between December 2019 and March–September 2020. This article assesses the consequences of these rice price increases in Papua New Guinea (PNG), where 99% of rice is imported. Utilizing data from a PNG 2018 rural household survey along with earlier national household survey data, we examine rice consumption patterns in PNG and estimate demand parameters for urban and rural households. Model simulations indicate that a 25% rise in the world price of rice would reduce total rice consumption in PNG by 14% and reduce rice consumption of the poor (bottom 40% of total household expenditure distribution) by 15%. Including the effects of a possible 12% decrease in household incomes because of the COVID‐19 related economic slowdown, rice consumption of the urban and rural poor fall by 20% and 17%, respectively. Maintaining functioning domestic supply chains of key staple goods is critical to mitigating the effects of global rice price increases, allowing urban households to increase their consumption of locally produced staples.